Norsk Ordbok – også ei elektronisk ordbok? - Bakken, Kristin; Ore, Christian-Emil (LexicoNordica, 2005)
The paper gives a short presentation of Norsk Ordbok (The Norwegian dictionary) as to scope and history. The recent computerization efforts have given the project a database with the data structured in a way that invites exploitation in the format of an electronic dictionary. The authors account for the information categories that are reflected in the new database, and on how these categories can be activated by the search system developed to access information from the database. It is argued that the database and the search system already constitutes an electronic dictionary, with the defined user group restricted to the editors for now. Made public, the authors think that the electronic dictionary both will obtain new users, and will be put to other uses than the paper version. In conclusion three focuses for future work are outlined. Firstly the project wants to present the dictionary integrated with its sources. Secondly, it is discussed how the user interface could accommodate different user groups, and finally it is commented on how a well designed crossreference system may be exploited for new kinds of searches.